2008
DOI: 10.5194/bg-5-215-2008
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient limitation of primary productivity in the Southeast Pacific (BIOSOPE cruise)

Abstract: Abstract.Iron is an essential nutrient involved in a variety of biological processes in the ocean, including photosynthesis, respiration and dinitrogen fixation. Atmospheric deposition of aerosols is recognized as the main source of iron for the surface ocean. In high nutrient, low chlorophyll areas, it is now clearly established that iron limits phytoplankton productivity but its biogeochemical role in low nutrient, low chlorophyll environments has been poorly studied. We investigated this question in the une… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
115
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(128 citation statements)
references
References 51 publications
12
115
1
Order By: Relevance
“…Nevertheless, in this area, picophytoplankton cell abundances (Grob et al 2007) and P incorporation rates also increased in the bottom layer of the euphotic zone (between 3 and 1% PAR). These results suggest that the majority of the picophytoplankton lived in the bottom layer of the euphotic zone, which was located at the vicinity of the nitracline, so enabling the smaller phytoplankton to take advantage of their large surface area to volume ratio to access N, the limiting nutrient in the SPG (Bonnet et al 2008). The accumulation of a picophytoplankton biomass at the level of 1% PAR is common to other oligotrophic gyres in the world's oceans (Teira et al 2005).…”
Section: Role Of Microorganisms In the Carbon Budgetmentioning
confidence: 84%
See 1 more Smart Citation
“…Nevertheless, in this area, picophytoplankton cell abundances (Grob et al 2007) and P incorporation rates also increased in the bottom layer of the euphotic zone (between 3 and 1% PAR). These results suggest that the majority of the picophytoplankton lived in the bottom layer of the euphotic zone, which was located at the vicinity of the nitracline, so enabling the smaller phytoplankton to take advantage of their large surface area to volume ratio to access N, the limiting nutrient in the SPG (Bonnet et al 2008). The accumulation of a picophytoplankton biomass at the level of 1% PAR is common to other oligotrophic gyres in the world's oceans (Teira et al 2005).…”
Section: Role Of Microorganisms In the Carbon Budgetmentioning
confidence: 84%
“…In the oligotrophic area, nitrate concentrations were < 3 nmol l -1 while DIP concentrations were >120 nmol l -1 . Primary and bacterial productions were shown to be N-limited , Bonnet et al 2008.…”
Section: Methodsmentioning
confidence: 99%
“…The Equatorial Pacific Upwelling Region sampled here has been shown to have extremely low available iron (≤0.1 nM) and is thought to limit phytoplankton growth (40,41). Part of the Indian Ocean gyre may also be iron limited (42,43), although the BEC model suggests otherwise (22).…”
Section: Discussionmentioning
confidence: 98%
“…Iron addition experiments carried out in the Eastern Equatorial Pacific found that most phytoplankton, including marine Synechococcus, underwent rapid growth upon addition of iron (41,(45)(46)(47). The most striking exception was Prochlorococcus, which showed only a minimal response both in growth and fluorescence to iron enrichment.…”
Section: Discussionmentioning
confidence: 99%
“…It supports high N 2 fixation rates (235 µmol N m −2 d −1 ; Garcia et al, 2007), high Trichodesmium sp. (Dupouy et al, 2000;Le Borgne, 2008, 2010) and UCYN abundances (Biegala and Raimbault, 2008). This site therefore represented an ideal location to investigate the fate of DDN.…”
Section: Introductionmentioning
confidence: 99%